2018
DOI: 10.1038/s41598-018-32155-1
|View full text |Cite
|
Sign up to set email alerts
|

Human-like smelling of a rose scent using an olfactory receptor nanodisc-based bioelectronic nose

Abstract: We report a strategy for the human-like smelling of a rose scent utilizing olfactory receptor nanodisc (ND)-based bioelectronic nose devices. In this strategy, a floating electrode (FE)-based carbon nanotube (CNT) field effect transistor (FET) was functionalized with human olfactory receptor 1A2 (hOR1A2)-embedded NDs (hOR1A2NDs). The hOR1A2NDs responded to rose scent molecules specifically, which were monitored electrically using the underlying CNT-FET. This strategy allowed us to quantitatively assess the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 59 publications
(77 reference statements)
2
23
0
Order By: Relevance
“…Receptomics research with microfluidic receptor cell arrays aims to measure purely biological responses without a complicated biological system surrounding it [13]. For example, the human tongue can be emulated on a chip by an array containing G-protein coupled receptors (GPCRs), e.g ., in the form of reconstituted receptor proteins [4] or vesicles [5]. Another possibility is formed by living cells expressing the genes coding for particular GPCRs, produced by either reverse-transfecting a generic cell line on the chip [6] or spotting pre-transfected cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…Receptomics research with microfluidic receptor cell arrays aims to measure purely biological responses without a complicated biological system surrounding it [13]. For example, the human tongue can be emulated on a chip by an array containing G-protein coupled receptors (GPCRs), e.g ., in the form of reconstituted receptor proteins [4] or vesicles [5]. Another possibility is formed by living cells expressing the genes coding for particular GPCRs, produced by either reverse-transfecting a generic cell line on the chip [6] or spotting pre-transfected cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although the benefits of rose oil are known to be mediated through the olfactory system [ 39 ], OR involvement is rarely mentioned. However, the activation of an OR (hOR1A2) with molecules present in a rose oil was already investigated [ 40 ] and the authors showed that citronellol and geraniol activate this receptor. Here, for the first time, we confirm that a rose extract activates skin ORs.…”
Section: Discussionmentioning
confidence: 99%
“…hOR, human odorant receptor; DmelOR, Drosophila melanogaster odorant receptor; MDL, minimum detection limit. Data cited from: Jin et al [35]; Goldsmith et al [36]; Yang et al [46]; Lee et al [47]; Murugathas et al [48]; Khadka et al [49]; Sung et al [50]; Lim et al [51]; Oh et al [52]; Park et al [53]; and Ahn et al [54].…”
Section: Or-based Bioelectronic Nosementioning
confidence: 99%
“…Application of the device in food spoilage was also demonstrated, as shown in Figure 3. In a recent publication by the same group, a human OR was used for the electronic detection of a rose scent with a reported sensitivity in the fM range [47]. Biosensing with nanodisc-embedded insect ORs was recently demonstrated using multiple Drosophila melanogaster (fruit fly) ORs: OR10a, OR22a, OR35a, and OR71a.…”
Section: Nanodiscsmentioning
confidence: 99%